2021
DOI: 10.3390/cells10082059
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Signaling in Cancer Cells: What Makes LPA So Special?

Abstract: Lysophosphatidic acid (LPA) refers to a family of simple phospholipids that act as ligands for G protein-coupled receptors. While LPA exerts effects throughout the body in normal physiological circumstances, its pathological role in cancer is of great interest from a therapeutic viewpoint. The numerous LPA receptors (LPARs) are coupled to a variety of G proteins, and more than one LPAR is typically expressed on any given cell. While the individual receptors signal through conventional GPCR pathways, LPA is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 189 publications
2
30
0
Order By: Relevance
“… If the gene is associated with prostate cancer (PCa) or enzalutamide-resistant (ER) according to literature search ( Wu et al, 2006 ; Tam et al, 2007 ; Lin et al, 2015 ; Wang et al, 2018 ; Handle et al, 2019 ; Chen et al, 2020 ; Kase et al, 2020 ; Balijepalli et al, 2021 ; Dickson et al, 2021 ; Furlan et al, 2021 ), a ○ is placed in the corresponding entry. The p -value of each gene is computed by Wilcoxon rank-sum test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… If the gene is associated with prostate cancer (PCa) or enzalutamide-resistant (ER) according to literature search ( Wu et al, 2006 ; Tam et al, 2007 ; Lin et al, 2015 ; Wang et al, 2018 ; Handle et al, 2019 ; Chen et al, 2020 ; Kase et al, 2020 ; Balijepalli et al, 2021 ; Dickson et al, 2021 ; Furlan et al, 2021 ), a ○ is placed in the corresponding entry. The p -value of each gene is computed by Wilcoxon rank-sum test.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, based on gene expression data and additional biological knowledge, we propose a novel differential network estimation method named weighted joint sparse penalized D-trace model (WJSDM), to infer the changes of gene regulatory networks between two different states. By employing D-trace loss function and using a revised Kendall's tau correlation, our method can directly infer the differential network between two different states from gene expression data with missing (Wu et al, 2006;Tam et al, 2007;Lin et al, 2015;Wang et al, 2018;Handle et al, 2019;Chen et al, 2020;Kase et al, 2020;Balijepalli et al, 2021;Dickson et al, 2021;Furlan et al, 2021) values. Furthermore, to integrate the gene expression data collected from different data platforms and utilize the information provided by various prior biological knowledge, we propose a weighted group bridge penalty function, which enable our model to draw support from multiple related data sets.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of LPA are mediated by six specific GPCRs, namely LPAR 1-6, and two unspecific GPCRs-the GPR87 and P2Y5 receptors. Specific LPA receptors are coupled to the G s , G i/o , G q/11 , and/or G 12/13 proteins [130]. Interestingly, it was observed that MCs express the LPAR1-5 gene [131].…”
Section: Bioactive Lipids As Key Molecules Involved In Mc-tumor Interactionsmentioning
confidence: 99%
“…LPA is generated either by hydrolysis of LPC by ATX or via the de novo pathway of glycerol 3-phosphate esterification by glycerol-3-phosphtae acyltransfarase-1 (GPAT-1). ATX, LPAR1 and LPAR2 are overexpressed in different tumor types, including ovarian cancer, osteocarcinoma, metastatic melanoma, neuroblastoma, breast cancer, pancreatic cancer, prostate cancer, and hepatocellular carcinoma [ 43 , 60 ]. Expression of ATX and/or LPAR can be further increased upon chemo- or radiotherapy, as shown for breast cancer [ 44 , 61 ].…”
Section: Biological Prospective Of Atx-lpar1 Dual Inhibitionmentioning
confidence: 99%